Power and Efficiency Analysis of Diesel Cycle Under Alternative Criteria - GÜMÜŞ, METİN; ATMACA, MUSTAFA (SPRINGER HEIDELBERG, 2014)
Model studies of the internal combustion engine cycles are useful for illustrating some important parameters affecting engine performance. The Diesel cycle is considered as a special case of an internal combustion engine. In the diesel cycle, combustion is controlled in order to obtain constant pressure at the beginning of the expansion stroke. It is important to choose the proper optimization criterion for the optimum design of the internal combustion engines. The choice of optimization criterion can be changed depending on the purpose of engine design and working conditions of the internal combustion engine. In this study, a comparative performance analysis is carried out for a reversible air standard Diesel cycle based on three alternative performance criteria, namely, maximum power (mp), maximum power density (mpd) and maximum efficient power (mep). The effects of the design parameters such as volume ratio and extreme temperature ratio of the cycle have been investigated under mp, mpd, mep and maximum efficiency conditions. The results show that the design parameters at mep conditions lead to more efficient engines than that at the mp conditions and that the mep criterion may have a significant power advantage compared to mpd criterion.
Keywords: Diesel cycle; Maximum efficient power; Maximum power; Maximum power density; Performance optimization; HEAT-ENGINE CYCLES; IRREVERSIBLE DUAL-CYCLE; VARIABLE SPECIFIC-HEATS; PERFORMANCE ANALYSIS; WORKING FLUID; EXHAUST-GAS; OTTO-CYCLE; OPTIMIZATION; TEMPERATURE; FRICTION